Pharmacokinetics of Full Length and Two-Domain Tissue Factor Pathway Inhibitor in Combination with Heparin in Rabbits - Bregengaard, Claus; Nordfang, Ole; Østergaard, Per; Petersen, Jens G L; Meyn, Giorgio; Diness, Viggo; Svendsen, Ove; Hedner, Ulla (Thrombosis and Haemostasis, 1993)
Tissue factor pathway inhibitor (TFPI) is a feed back inhibitor of the initial activation of the extrinsic pathway of coagulation. In humans, injection of heparin results in a 2-6 fold increase in plasma TFPI and recent studies suggest that TFPI may be important for the anticoagulant activity of heparin. Full length (FL) TFPI, but not recombinant two-domain (2D) TFPI, has a poly cationic C-terminus showing very strong heparin binding. Therefore, we have investigated if heparin affects the pharmacokinetics of TFPI with and without this C-terminus.FL-TFPI (608 U/kg) and 2D-TFPI (337 U/kg) were injected intravenously in rabbits with and without simultaneous intravenous injections of low molecular weight heparin (450 anti-XaU/kg).Heparin decreased the volume of distribution and the clearance of FL-TFPI by a factor 10-15, whereas the pharmacokinetics of 2D-TFPI were unaffected by heparin. When heparin was administered 2 h following TFPI the recovery of FL-TFPI was similar to that found in the group receiving the two compounds simultaneously, suggesting that the releasable pool of FL-TFPI is removed very slowly in the absence of circulating heparin.